Bibliometric Analysis of the Interconnection Between Global Trade and Exchange Rate Policies - Judijanto, Loso; Ekowati, Dhiana (Eastasouth Institute, 2024)
This study conducts a bibliometric analysis to explore the intricate relationships between global trade and exchange rate policies. Utilizing data extracted from major academic databases, the research synthesizes relevant literature from the past three decades to identify key thematic areas, influential authors, and the evolution of research trends over time. The analysis reveals how exchange rate volatility impacts global trade dynamics, highlights the theoretical underpinnings such as the Mundell-Fleming model and the Purchasing Power Parity, and identifies gaps in the current literature. The study's findings provide significant insights into the role of exchange rate management in economic stability and the interconnectedness of global markets. Practical implications are discussed with a focus on policy formulation and strategic financial management, while theoretical contributions offer enhancements to existing economic frameworks and propose new areas for empirical research. This research not only enriches the academic field of international economics but also serves as a foundational resource for policymakers and economic strategists navigating the complexities of global trade.